The effect of warm compress and aromatherapy lavender to decreasing pain on primary dysmenorrhea - Yunianingrum, Esti; Widyastuti, Yani; Margono, Margono (Jurnal Kesehatan Ibu dan Anak, 2018)
Primary dysmenorrhea is menstrual pain that occurs since menarche without a pelvic pathology condition causing disruption of daily activity and decreasing quality of life. Improved blood circulation and aromatic smell can reduce pain.This study aim to know the different mean decrease pain of primary dysmenorrhea in given warm compress and aromatherapy lavender.This study was quasi experimental design. The subjects of this study was adolescents of 44 respondents who suffered of dysmenorrhea and met the criteria. The results of this study indicate that  the mean of primary dysmenorrhea pain before and after given warm compress is 6.05 ± 1.046 and 3.55 ± 1.335 with mean decrease of 2.5, it means there was influence of giving warm compress to decrease of primary dysmenorrhea pain (p = 0,000). The mean of primary dysmenorrhea pain before and after lavender aromatherapy was 5.95 ± 1.214 and 4.77 ± 1.232 with a mean decrease of 1.18, it means there was an effect of lavender aromatherapy on decreasing primary dysmenorrhea pain (p = 0.000). Mann Whitney test obtained results p = 0.000, means there were differences dysmenorrhea pain reduction with warm compresses and aromatherapy lavender. Warm compresses are more effective in reducing primary dysmenorrhea pain.